The Contribution of Physical Education Teachers in Shaping Student Character - Permana, Gilang; Carsiwan, Carsiwan; Juliantine, Tite; Yulianto, Ari Gana; Aman, Mohd Salleh; Shahudin, Nurul Nadiah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study is a literature review aimed at understanding the contribution of physical education teachers in shaping students' character. The method used in this research is a literature review, with research sources obtained from various references such as journals, books, documentation, the internet, libraries, and other relevant sources. The data collection technique for this literature review involved gathering various references and citations relevant to the research topic, utilizing the Google Scholar database by entering the keyword “contribution of physical education teachers in building student character.” The database search yielded 10 articles published between 2016 and 2022 that are relevant to the focus of this study. The findings indicate that physical education plays a significant role in shaping and instilling character in students. It can be concluded that the contribution of physical education teachers is currently at a moderate level in the process of character development in students. Therefore, it is expected that physical education teachers will further enhance their contributions to the implementation of character education.